Six Weeks of Polarized Versus Moderate Intensity Distribution: A Pilot Intervention Study - Röhrken, Golo; Held, Steffen; Donath, Lars (Frontiers in Physiology, 2020)
Background Previous research indicates that polarized training-intensity-distribution (TID) programs could enhance endurance performance. Short-distance triathletes, however, perform most of their competition-specific training around moderate-intensity intervals. There is still a lack of evidence as to which program is more beneficial during triathlete training. This pilot study examined 6 weeks of training-macrocycle using polarized intensity distribution compared to moderate TID and it’s effects on sub-maximal and maximal performance indices during running and cycling. Methods Fifteen moderately trained triathletes were either assigned to an intervention group (INT, n = 7, 2 females/5 males, Age: 29.1 ± 7.6) or a control group (CON, n = 8, 2 females/6 males, Age: 30.3 ± 6.1). We used the minimization method (Strata: gender, age competition times, training volumes) to allocate the groups. The participants underwent incremental cycling and running testings before and after the intervention period to assess performance indices until objective exhaustion. CON employed a moderate TID with either medium-intensity (MIT) or low-intensity training (LIT). INT used polarized training intensity distribution (TID), with either LIT or high-intensity training (HIT). Average training hours and anthropometric data did not indicate any differences between CON and INT during the study period. We applied the polarization index of >2 in INT (2.1 ± 0.4) and <1 in CON (0.9 ± 0.3). Results Both groups notably improved their lactate threshold 2 (+2.8 ± 5.1 %, p = 0.026) and peak (+5.4 ± 6.2 %, p = 0.002) running performance. We did not observe statistically significant time × group interaction effects in any of the performance outcomes between both groups. Conclusion Polarized TID in moderately trained triathletes did not prove to be superior compared to a more moderate TID. However, more studies in larger and more highly trained subjects are needed.